Fast and slow-twitching muscles are differentially affected by reduced cholinergic transmission in mice deficient for VAChT: A mouse model for congenital myasthenia. (November 2018) - Magalhães-Gomes, Matheus P.S.; Motta-Santos, Daisy; Schetino, Luana P.L.; Andrade, Jéssica N.; Bastos, Cristiane P.; Guimarães, Diogo A.S.; Vaughan, Sydney K.; Martinelli, Patrícia M.; Guatimosim, Silvia; Pereira, Grace S.; Coimbra, Candido C.; Prado, Vânia F.; et al.
Abstract: Congenital myasthenic syndromes (CMS) result from reduced cholinergic transmission at neuromuscular junctions (NMJs). While the etiology of CMS varies, the disease is characterized by muscle weakness. To date, it remains unknown if CMS causes long-term and irreversible changes to skeletal muscles. In this study, we examined skeletal muscles in a mouse line with reduced expression of Vesicular Acetylcholine Transporter (VAChT, mouse line herein called VAChT-KD HOM ). We examined this mouse line for several reasons. First, VAChT plays a central function in loading acetylcholine (ACh) into synaptic vesicles and releasing it at NMJs, in addition to other cholinergic nerve endings. Second, loss of function mutations in VAChT causes myasthenia in humans. Importantly, VAChT-KD HOM present with reduced ACh and muscle weakness, resembling CMS. We evaluated the morphology, fiber type (myosin heavy chain isoforms), and expression of muscle-related genes in the extensor digitorum longus (EDL) and soleus muscles. This analysis revealed that while muscle fibers atrophy in the EDL, they hypertrophy in the soleus muscle of VAChT-KD HOM mice. Along with these cellular changes, skeletal muscles exhibit altered levels of markers for myogenesis (Pax-7, Myogenin, and MyoD), oxidative metabolism (PGC1-α and MTND1), and protein degradation (Atrogin1 and MuRF1) in VAChT-KD HOM mice. Importantly, we demonstrate that deleterious changes in skeletal muscles and motor deficits can be partially reversed following the administration of the cholinesterase inhibitor, pyridostigmine in VAChT-KD HOM mice. These findings reveal that fast and slow type muscles differentially respond to cholinergic deficits. Additionally, this study shows that the adverse effects of cholinergic transmission, as in the case of CMS, on fast and slow type skeletal muscles are reversible. Graphical abstract: Highlights: Atrophy of the fast-EDL and hypertrophy of the slow-Soleus muscles from a VAChT Knockdown, homozygous mice (VAChT KD HOM ). Cholinergic dysfunction induces fiber type switching in EDL and Soleus and causes myofibrils ultrastructure abnormalities. VAChT KD HOM mice presented altered levels of markers for myogenesis, oxidative metabolism and protein degradation. The muscle waste in this type of congenital myasthenia may be rescuable following pyridostigmine treatment.